Diseño de un sistema de costo basado en actividades (ABC) para la línea de producción alimenticia de la asociación de mujeres creciendo con fondo ecuatoriano POPULORUM progresivo (FEPP). - Loor Crespin, Fabiola Alexandra (2019)
The "Association of Women Growing with Ecuadorian Populorum Progressive Fund (FEPP)" during its existence has had the following problems mainly: it lacks a defined method of establishing costs and does not have an established cost process. This document presents the description of each of the stages carried out in the Association of Women Growing with FEPP with the objective of designing an ABC Cost System so that the administrative bodies of that organization have the possibility of adopting a costing model that allowed to know the real productive cost based on each of the activities that are executed as a production process. First, an initial diagnosis was made to identify how the organization is established and structurally organized in all its aspects through the investigative technique of observation, as well as an in-depth analysis of production costs in each of its products. Subsequently, the entire productive process of the company was characterized in a detailed manner with the objective of implementing and designing the "ABC Cost System". The design of the Cost System includes the definition of each of the activities, identifying cost drivers and relating them to each of the activities. Subsequently, the labor costs were distributed based on the observation of time and the indirect costs of manufacturing based on the inductors, and finally the office tool (Excel) was developed, which facilitates the calculation and management of costs under the proposed system.